2019
DOI: 10.3390/genes11010028
|View full text |Cite
|
Sign up to set email alerts
|

Coding-Gene Coevolution Analysis of Rotavirus Proteins: A Bioinformatics and Statistical Approach

Abstract: Rotavirus remains a major cause of diarrhea in infants and young children worldwide. The permanent emergence of new genotypes puts the potential effectiveness of vaccines under serious question. The distribution of unusual genotypes subject to viral fitness is influenced by interactions among viral proteins. The present work aimed at analyzing the genetic constellation and the coevolution of rotavirus coding genes for the available rotavirus genotypes. Seventy-two full genome sequences of different genetic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 85 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…For RVA replication, VP1 is an RNA-directed RNA polymerase (RdRp) and can be considered the masterpiece for viral replication. We reported that most of the coevolving residues in VP1 are located in the RNA entry tunnel . Additional structural analysis of RVA proteins upon mutations may enhance our ability to better understand the role of residues in the entry tunnel of RVA VP1 in viral replication.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…For RVA replication, VP1 is an RNA-directed RNA polymerase (RdRp) and can be considered the masterpiece for viral replication. We reported that most of the coevolving residues in VP1 are located in the RNA entry tunnel . Additional structural analysis of RVA proteins upon mutations may enhance our ability to better understand the role of residues in the entry tunnel of RVA VP1 in viral replication.…”
Section: Introductionmentioning
confidence: 97%
“…It is a significant cause of childhood gastroenteritis and accounts for ∼450,000 deaths annually, most occurring in developing countries . RVA also causes a great economic loss to the livestock industry worldwide, mostly in the developing countries. , In our previous work, we reported a complex network of coevolving residues for RVA genes of different genetic constellations using advanced genomic analysis . For RVA replication, VP1 is an RNA-directed RNA polymerase (RdRp) and can be considered the masterpiece for viral replication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations